2010
DOI: 10.1021/bc1003058
|View full text |Cite
|
Sign up to set email alerts
|

Photocleavable Peptide-Conjugated Magnetic Beads for Protein Kinase Assays by MALDI-TOF MS

Abstract: Peptides were immobilized onto superparamagnetic beads via photocleavable linkers. This enabled simple, rapid, and label-free protein kinase assays via MALDI-TOF MS detection of substrate peptide phosphorylation. Abltide, a model substrate for the Abl protein tyrosine kinase model, was coupled onto amine-terminated beads, incubated with ATP and recombinant c-Abl kinase, and released and further detected to determine phosphorylation. Abltide phosphorylation was found to depend significantly on the length and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Nonetheless, optimal MALDI matrices for ionization of peptides and oligonucleotides are distinct and the ionization properties of peptide-oligonucleotide conjugates and particularly of phosphorylated conjugates are unpredictable. Toward obviating this confounding factor, we drew on prior studies 25, 29 that demonstrated that a photocleavable cross-linker could be introduced to provide reliable detection of peptide phosphorylation by MALDI-TOF MS.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, optimal MALDI matrices for ionization of peptides and oligonucleotides are distinct and the ionization properties of peptide-oligonucleotide conjugates and particularly of phosphorylated conjugates are unpredictable. Toward obviating this confounding factor, we drew on prior studies 25, 29 that demonstrated that a photocleavable cross-linker could be introduced to provide reliable detection of peptide phosphorylation by MALDI-TOF MS.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that magnetic beads are a powerful tool for hybrid and solid-phase protein kinase assays, offering separation and suitability to automated procedures as well as favorable analysis by MALDI-TOF MS. 2425 To pull out protein kinase products from kinase reaction mixtures by magnetic beads through DNA hybridization for detecting degree of phosphorylation, we investigated the immobilization of the complementary thiol-modified oligonucleotide (5′-HS GTACTTCCTTAAACGACGCAGG-3′) on magnetic beads. First, to prevent nonspecific interactions, a poly(ethylene glycol) (PEG) spacer linker was grafted onto the surface of magnetic beads according as previously reported (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations